Social Epidemiology Study on Community Preventive Behavior in Facing the Global Health Crisis - Andi Nurhalizah Tenriyola, AP (Journal of Public Health Indonesian, 2025)
This study examines community preventive behavior during global health crises from a social epidemiology perspective, emphasizing the roles of social determinants, institutional trust, and structural inequality. A critical integrative literature review was conducted using thematic analysis of 45 publications indexed in PubMed, Scopus, ScienceDirect, SpringerLink, and Google Scholar, published between 2019 and 2025. The synthesis shows that preventive behavior is not merely a function of knowledge or individual motivation, but is consistently patterned along lines of education, income, employment status, and access to credible information. Populations in structurally disadvantaged positions tend to display markedly lower preventive capacity, while higher levels of institutional trust are associated with more consistent adherence to recommended measures. Yet, much of the existing scholarship still privileges individual psychological determinants, leaving insufficient attention to how macro-level social structures and trust dynamics jointly shape collective compliance and health resilience. This article addresses that gap by developing an integrated conceptual model that connects social epidemiology, structural inequality, and trust theory to explain preventive behavior during global crises. The study contributes theoretically by reframing prevention as a socially produced capability rather than an isolated individual choice, and practically by offering a framework to reorient public health policy toward structural equity, trust-building, and socially grounded risk communication as foundations for sustainable collective prevention